2019
DOI: 10.1590/1413-81232018241.35302016
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar psicológico en las personas mayores no dependientes y su relación con la autoestima y la autoeficacia

Abstract: Resumen Este estudio tuvo como objetivo examinar las relaciones entre el bienestar psicológico, la autoeficacia para envejecer y la autoestima en personas mayores de 60 años no dependientes. Han participado 148 personas con edades comprendidas entre 60 y 96 años, completando una batería de instrumentos relacionados con la autonomía, el grado y tipo de actividad, la autoeficacia para afrontar el proceso de envejecimiento, la autoestima y el bienestar psicológico. Los resultados indican que el bienestar psicológ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
1
10
0
18
Order By: Relevance
“…Finally, the present study corroborates the role of subjective well-being in the perception of the general health of the elderly, showing how satisfaction with life experienced by the elderly positively predicts their general health. Previous studies in elderly people have presented similar results, showing that when older persons feel satisfied with their lives, they are more likely to feel high self-esteem and good perceived general health [11,31,39,46]. In the present study, self-esteem has not turned out to be a positive predictor of the perception of health, so a greater analysis of these variables is required in future studies.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Finally, the present study corroborates the role of subjective well-being in the perception of the general health of the elderly, showing how satisfaction with life experienced by the elderly positively predicts their general health. Previous studies in elderly people have presented similar results, showing that when older persons feel satisfied with their lives, they are more likely to feel high self-esteem and good perceived general health [11,31,39,46]. In the present study, self-esteem has not turned out to be a positive predictor of the perception of health, so a greater analysis of these variables is required in future studies.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, it has been observed that age positively predicts the perception of social support, which in turn predicts the experiences of well-being and the general perception of the health of the elderly. However, previous literature has shown that old age reduces the social support network available [28,31,43]. Future studies need to analyze these relationships to understand better the factors that may interfere with their relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta dimensión es considerada como la forma de expresar los pensamientos y sentimientos positivos que se construye la persona sobre el mundo que los rodea y sobre sí mismo, que se relaciona con las vivencias que experimenta el hombre y el valor subjetivo que le da. Autoaceptación: Es la manera consciente de realizar evaluaciones de la vida pasada, reconocer los diferentes aspectos de uno mismo y aceptar nuestras limitaciones y aun así asumirlo con actitud positiva (Vázquez et al, 2009;Mesa-Fernández et al, 2019).…”
unclassified
“…Por otro lado, la postura eudaimónica y hedónica están relacionado con la activación de la corteza pre-frontal, en especial con el lado izquierdo (Urry et al, 2004). Además en lo referente a su asociación con la salud psicológica, la postura eudaimónica reduce el riesgo del desarrollo de las enfermedades mentales (Mjosund et al, 2015), asimismo, está relacionado con altos niveles de felicidad, auto-aceptación, adecuadas relaciones interpersonales, autonomía, desarrollo de las capacidades para afrontar problemas y con un nivel adecuado de autoestima (Hun, Urzúa, López, Escobar & Leiva, 2019;Mesa, Pérez, Nunes & Menéndez, 2019;Muratori et al, 2015;Uribe, Ramos, Villamil & Palacio, 2018).…”
Section: Bienestar Psicológicounclassified